Model Bisnis Platform Kecantikan Beaudy Sebagai Media Telekonsultasi Perantara Antara Consumer Dengan Klinik Kecantikan - Evarianti Evarianti; Kustini Kustini (Pusat Riset dan Inovasi Nasional, 2023)
Currently, the business platform model is experiencing rapid development, one of which is in the health sector. The purpose of establishing a platform is to make it easier for consumers to be able to exchange value with one another. The idea for the Beaudy beauty business platform model is to help customers solve their skin problems. Customers who have problems in conducting skin care consultations, starting from price consultations tend to be expensive and don't have time to go to a beauty clinic. So that the results of the validation of the solutions carried out to the informants were the idea of a Beaudy web-based beauty business platform model that could help and answer the problems they were experiencing. These results indicate that Beaudy can be an intermediary teleconsultation medium between consumers and beauty clinics.